(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Thermal power plants (PPPs) are the basis of electric energy; they produce electricity as a result of the conversion of thermal energy released during the burning of organic fuel. According to the type of electrical equipment, thermal power plants are divided into steam turbine, gas turbine and diesel power plants.